Anaerobic fermentative co-production of hydrogen and methane from an organic fraction of municipal solid waste - Dong, Li; Zhenhong, Y.; Yongming, S.; Longlong, M. (Taylor & Francis, 2011)
In order to improve energy recovery efficiency, the fermentative hydrogen production from organic fraction of municipal solid waste was followed by methane production using the residual of hydrogen production as a substrate. Six individual components of organic fraction of municipal solid waste, including rice, potato, lettuce, lean meat, peanut oil, and banyan leaves, were selected as experimental materials. The results showed that at the hydrogen production stage, the hydrogen yields were 125, 103, 35, 0, 5, and 0 mL/gVS for rice, potato, lettuce, lean meat, peanut oil, and banyan leaves, respectively. During the methane production stage, the methane yields were 232, 237, 148, 278, 866, and 50 mL/gVS. For example, for rice the co-production of hydrogen and methane increased the energy efficiency from 7.9 to 56.3% compared with single hydrogen production. Copyright © 2011 Taylor & Francis Group, LLC.